Dampak Kesenjangan Jam Bekerja terhadap Ketimpangan Upah di Jabodetabek Selama Pandemi Covid-19 Tahun 2020 - Jannah, Sophia Lailil; Rini, Ariska Nurfajar (UI Scholars Hub, 2024)
This study aims to analyze the differences in working hours of male and female workers on the wage gap during the Covid-19 Pandemic in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) area in 2020 using the Ordinary Least Square (OLS) and the Blinder-Oaxaca Decomposition. Utilizing the National Labor Force Survey (SAKERNAS) 2020, the results showed that working hours positively and significantly affected wages with a coefficient of 4.72% for male workers and 7.05% for female workers. The Blinder-Oaxaca decomposition proved that working hours contribute to reducing the wage gap because there is wage convergence due to reduced working hours during the implementation of the Large-Scale Social Restrictions policy in Jabodetabek.